Identification of CAND1 as a DNA-dependent protein kinase-regulated coactivator of androgen receptor and the ARv7 splice variant - Ross A. Hamilton; Basil Paul; Ping Yi; Kimal Rajapakshe; Anil K. Panigrahi; Sandra L. Grimm; Cristian Coarfa; Anna Malovannaya; Nancy L. Weigel; David M. Lonard; Charles E. Foulds (PLoS ONE, 2026)
ARv7, the most prevalent androgen receptor (AR) variant in castration-resistant prostate cancer, lacks the ligand binding domain (LBD), rendering it resistant to LBD-targeted therapies. Identifying new therapeutic targets requires defining the coregulators and associated regulatory enzymes that govern AR and ARv7 transcriptional activity. Here, we have developed a cell-free DNA pulldown assay employing androgen response elements (AREs) to isolate and characterize the AR- and ARv7-associated coregulator complexes formed on DNA. Mass spectrometry analyses of ARE DNA pulldowns revealed previously unrecognized AR and ARv7 associating coregulators, such as cullin-associated NEDD8-dissociated protein 1 (CAND1), in addition to previously known coregulators. ARv7 showed enhanced recruitment of a subset of AR associating coregulators. Knockdown of CAND1 in prostate cancer cells reduced the expression of AR and ARv7 target genes, supporting its role as a coactivator. Bioinformatic analyses of human prostate cancer clinical datasets revealed that CAND1 mRNA level correlated with disease status, with higher expression correlated with metastatic prostate cancer and poorer patient survival. We further show that DNA-dependent protein kinase (DNA-PK) phosphorylates both AR and ARv7, enhances their transcriptional activities, and stabilizes the interaction of CAND1 with AR- and ARv7- coregulator complexes. Collectively, these findings suggest that DNA-PK stimulates the AR and ARv7 activity through its enzymatic function and by stabilizing (or reinforcing) coactivator interactions, including those involving CAND1. In sum, this work advances our understanding of AR isoform actions and identifies additional potential therapeutic targets for castration-resistant prostate cancer.